A new species of Oxyporus Fabricius (Coleoptera: Staphylinidae: Oxyporinae) from western Mexico and new record from Aguascalientes for O. mexicanus Fauvel - Navarrete-Heredia, José L.; Reyes-Hernández, José L. (Zootaxa, 2026)
A new species, Oxyporus amigo, is described from Jalisco and Michoacán, Mexico. The new species is diagnosed and illustrated. Additionally, Oxyporus mexicanus Fauvel, 1865 is recorded for the first time from the state of Aguascalientes, based on specimens collected in Monte Grande, San José de Gracia.